EFFICIENCY OF OZONE THERAPY IN GYNECOLOGY - Бубнова, Лидия Евгеньевна; Алексеева, Наталья Викторовна; Иванов, Леонид Николаевич; Павлова, Олимпиада Вячеславовна; Бубнов, Дмитрий Николаевич; Давыдова, Нелли Юрьевна (Medicine in Kuzbass, 2022)
In the structure of gynecological diseases of the pelvic organs, inflammatory processes occupy a leading position, accounting for 60-65 % of the total number of applicants. Non-drug therapy occupies its solid niche among the means of treating many diseases and relapses of the urogenital tract.One of the non-medical means of treatment is medical ozone, the use of which demonstrates its effectiveness in obstetrics and gynecology.According to the results of our research, the complex use of parenteral ozone therapy for therapeutic purposes aimed at normalizing violations of lipid peroxidation processes, correcting all links of immunity, eliminating pain syndrome and reducing all links of immunity, eliminating of the urogenital tract. When comparing the average values of the immunological of cellular and humoral immunity significantly improve, vascular disorders are eliminated not only in the focus of inflammation, but also in the body as a whole.Inflammatory diseases of the pelvic organs remain an acute medical and socio-economic problem that requires practical medicine to activity search for new effective therapeutic schemes, which is parenteral ozone therapy, which contributes to the preservation of reproductive function, reducing the risk of chronic inflammation, improving the quality of the life and sexual activity.
Keywords: medical ozone; ozone therapy; immunoreactivity; coagulogramm; products of lipid peroxidation